2019
DOI: 10.1136/bmjgh-2019-001658
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of infant and under-five mortality rates: a multivariate decomposition analysis of Demographic and Health Surveys in Ghana, 2003, 2008 and 2014

Abstract: IntroductionDespite the decline in infant and under-five mortality rates since the last decade, Ghana did not meet the millennium development goal (MDG) 4 target. To implement effective interventions that could fast-track progress towards achieving the sustainable development goal 3 in 2030, factors contributing to the decline in child mortality throughout the MDG period and which factor(s) has/have been consistent in affecting child survival in the last decade need to be understood.MethodsThis study used Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 34 publications
(32 reference statements)
12
26
0
Order By: Relevance
“…With regard to plurality, children born as multiple births had higher risk of under-five mortality as compared to singletons. This finding is consistent with other findings using 2011 EDHS data 19,20. In relation to size of child at birth, the odds of under-five mortality were higher for very small sized child at birth compared to average sized child at birth.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to plurality, children born as multiple births had higher risk of under-five mortality as compared to singletons. This finding is consistent with other findings using 2011 EDHS data 19,20. In relation to size of child at birth, the odds of under-five mortality were higher for very small sized child at birth compared to average sized child at birth.…”
Section: Discussionsupporting
confidence: 92%
“…[15] on geographical determinants of health in Ghana concluded that under‐five mortality rates are higher in rural than urban areas mainly because rural residents may not have equal access to preventive and curative services for their children [15]. Over time, however, the evidence from this study and another recent study [27] suggests that the rural‐urban gaps are narrowing. Interestingly, one study from 2014 that specifically focused on northern Ghana found that children in rural settings did not have an increased odds of under‐five mortality when compared to urban counterparts [14].…”
Section: Discussionmentioning
confidence: 70%
“…Too much focus on this subset unduly emphasises discrete, short-term and episodic efforts, often initiated or led from outside. But emerging evidence from several low-income and middle-income countries suggests that long-term change is brought about by local process, policies and dynamics—for example, the role of women’s empowerment in explaining long-term change in child health outcomes 38–41. It is unfair, and even misleading and colonial to pay undue attention to the foreign gaze.…”
Section: What If the Foreign Gaze Is Inconsequential?mentioning
confidence: 99%